A macroalgal germling bioassay to assess biocide concentrations in marine waters. Issue 1 (15th February 2015) - Girling, J.A.; Thomas, K.V.; Brooks, S.J.; Smith, D.J.; Shahsavari, E.; Ball, A.S.
Highlights: A bioassay method using germlings of macroalgae was developed to detect toxicity of anti-fouling paint biocides. Two macroalgae ( Ulva intestinalis and Fucus spiralis ) germlings were used to assess 4 common anti-fouling biocides. U. intestinalis germlings showed potential for the assessment of toxicity of anti-fouling paint biocides. Abstract: A bioassay method using the early life stages (germlings) of macroalgae was developed to detect toxicity of anti-fouling paint biocides. A laboratory based bioassay using Ulva intestinalis and Fucus spiralis germlings was performed with 4 common anti-fouling biocides (tributyltin (TBT), Irgarol 1051, Diuron and zinc sulphate), over a range of environmentally relevant concentrations (0.0033–10 μg l −1 ). Comparison between the two species showed that germlings of U . intestinalis were better adapted for in-situ monitoring, as germlings of F . spiralis appeared to be too robust to display sufficient growth differences. The response of U. intestinalis germling growth appeared to reflect environmental biocide concentrations. Overall the developed method showed potential for the assessment of the sub-lethal effects of anti-fouling biocides on the early developmental stages of U. intestinalis .